Burnout among caretakers of paediatric patient with chronic kidney disease in Hospital Universiti Sains Malaysia, Kelantan - Hazlan, Siti Nur Haidar (2021)
Taking care of a chronically ill patient is a stressful ordeal, especially in paediatric patient. Many studies have identified factors that may affect high stressor, but little study describes the prevalence of burnout among caretakers in chronically ill patients. It is well established that caretakers of children on chronic peritoneal dialysis have a significantly lower quality of life, and the prevalence of probable depression is also considerably more common. ⁽¹⁾ Caretaker or caregiver here denotes care given by family members or friends, rather than professional who is imbursed for their services. A caretaker has all the features of chronic stress experience due to multiple reasons that frequently require a high level of vigilance. It creates physical and psychological strain over extended periods accompanied by high levels of unpredictability and uncontrollability. These can create secondary stress in multiple life domains such as work and family relationships. ⁽²⁾ Burnout is a term first used in the 1970s by the American psychologist Herbert Freudenberger. There is a wide range of symptoms that is due to work-related or stress. One example of a source of stress outside of work is caring for a family member. There are three main areas that are considered to be symptoms of burnout. The symptoms are exhaustion, alienation from (work-related) activities, and reduced performance. The risk of depression is also increased in those with burnout.